2006
DOI: 10.1111/j.1939-1676.2006.tb01794.x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Relationship between Gastrointestinal Protein Loss, Gastric Ulceration or Erosion, and Strenuous Exercise in Racing Alaskan Sled Dogs

Abstract: These data suggest that relatively modest exercise is required to increase intestinal protein loss, but more substantial exercise is required to cause alterations in the proximal gastrointestinal tract. However, none of these alterations appear to progress with increasing exercise duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 9 publications
0
34
0
Order By: Relevance
“…The basis for choosing 100 miles in the previously reported study 1 was based upon prior findings that gastric lesions occurred as early as 100 miles and did not significantly increase in number or severity up to 500 miles. 5 The effectiveness of famotidine in that study plus the ease of administration of the drug associated with drug in the food as opposed to administering pills suggested that famotidine would be preferable to omeprazole under racing conditions over longer distances. The failure of administration of famotidine to significantly lessen the severity of gastric lesions in dogs running 330 miles in the 1st experiment was surprising after the efficacy documented in the previous study.…”
Section: Discussionmentioning
confidence: 92%
“…The basis for choosing 100 miles in the previously reported study 1 was based upon prior findings that gastric lesions occurred as early as 100 miles and did not significantly increase in number or severity up to 500 miles. 5 The effectiveness of famotidine in that study plus the ease of administration of the drug associated with drug in the food as opposed to administering pills suggested that famotidine would be preferable to omeprazole under racing conditions over longer distances. The failure of administration of famotidine to significantly lessen the severity of gastric lesions in dogs running 330 miles in the 1st experiment was surprising after the efficacy documented in the previous study.…”
Section: Discussionmentioning
confidence: 92%
“…However, because this test is not available routinely in commercial laboratories, it will not be detailed in this review. The test has been used experimentally to screen for gastric damage associated with nonsteroid antiinflammatory drugs, 24,25 gastric surgery, 26 or strenuous exercise 27 in dogs.…”
Section: Gastric Permeabilitymentioning
confidence: 99%
“…Since the main hemostatic finding was increased procoagulant activity, hemorrhage caused by systemically compromised hemostasis as part of the pathophysiology of the GI bleeding risk, reported in sled dogs, is less likely [1,4,21]. On the other hand prolonged hypercoagulable states associated with long distance racing activity could make dogs vulnerable to thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…The induction of increased procoagulant activity could be speculated to be caused by platelets activated by absorbed intestinal endotoxin [22], as increased intestinal permeability has been demonstrated in sled dogs [21,23] or by the proinflammatory state documented by the increased CRP after the 68 km sled pull. Other procoagulant activating mechanisms could include neutrophil activation, which in turn activates platelets and vice versa [24].…”
Section: Discussionmentioning
confidence: 99%